Spinaxinus (Bivalvia: Thyasiroidea) from sulfide biogenerators in the Gulf of Mexico and hydrothermal vents in the Fiji Back Arc: Chemosymbiosis and Taxonomy - Oliver, Graham (2015)
Two new species of the thyasirid genus Spinaxinus (S. emicatus Oliver n. sp. and S. phrixicus Oliver n. sp.) are described from the Gulf of Mexico and the southwest Pacific, respectively. Both are compared with the type species of the genus, the eastern Atlantic S. sentosus Oliver and Holmes, 2006. Living specimens from the Gulf of Mexico were retrieved from artificial sulfide bio-generators on the upper Louisiana Slope. Gill morphology and molecular markers from the symbiotic bacteria confirm that Spinaxinus is chemosynthetic and that the chemoautotrophic bacteria are related to sulfide oxidizing Gammaproteobacteria. Living specimens from the southwest Pacific were retrieved from hydrothermal vent sites in the Fiji and Lau Back Arc Basins. In the Atlantic Spinaxinus is now recorded from two anthropogenic situations and appears to be generally absent from natural cold seep sites and not yet recorded at any hydrothermal sites. The primarily anthropogenic distribution of Spinaxinus in the Atlantic is discussed with reference to the natural hydrothermal vent habitat of the Pacific S. phrixicus.